Future Proofing Tomorrow's Accounting Graduates: Skills, Knowledge and Employability - Michelle Anne O'Shea; Dorothea Bowyer; Gina Ghalayini (Australasian Accounting, Business and Finance Journal, 2022)
The future of work has generated robust debate among governments, industry, academics and social commentators. The intensity of these debates has extended to the accounting profession. Accordingly, and drawing on the experiences and interpretations of accounting professionals, tertiary students, and academics involved in a Work Integrated Learning (WIL) experience, the present research problematises tensions and gaps between employer skill and knowledge expectations and student interpretations of what employers want. The research unpacks how tertiary curriculum development and learning, and teaching practice innovations can meet employer skill and knowledge expectations. Key findings include students interpreting that highly developed technical skills and grades would enhance their post-degree employability. In contrast and problematically, employers were seeking graduates with highly developed soft skills. The research findings have significant implications for graduate employability and can inform contemporary tertiary accounting curriculum development.
Keywords: Employability; soft skills; work integrated learning; curriculum development